Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Dinas Komunikasi Informatika Dan Statistik Provinsi Riau Tahun 2023 - Rahakbauw, Oktovina Deci Rahakbauw; Adib, Muhammad (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the influence of the work environment, work motivation and job satisfaction on employee performance at the Riau Province Communications, Informatics and Statistics Service in 2023, either partially or simultaneously. Data collection was carried out using the Until Saturation method, the total population of which was 50 respondents at the Riau Province Communications, Informatics and Statistics Service. The data used in this research includes testing the validity of the variable Influence of the Work Environment, Work Motivation and Job Satisfaction on Employee Performance where the calculated r is greater than the r table of 0.2787. From the results of the reliability test using the Cronbach Alpha formula, there are results with r alpha values ​​> 0.6, namely r alpha Work Environment (0.900), Work Motivation (0.934) and Job Satisfaction (0.944) Employee Performance (0.867). The classical assumption test is used to strengthen multiple linear regression analysis by using 3 classical assumption tests, namely the normality test, multicollinearity test and heteroscedasticity test, where the 3 tests are free from the classical assumption test (fit test). The results of multiple linear regression analysis in this research are Y = 4.782 + 0.214 (LK) + 0.336 (MK) + 0.325 (KK) while the coefficient of determination (R²) is 0.668 or 66.8%, which means that the Work Environment, Work Motivation and Satisfaction Work on Employee Performance explains the variation in Employee Performance by 66.8%. The t test and F test show a significant effect both partially and simultaneously with the results of the t test Work Environment t count is greater than t table (2.162 > 2.01290) from Work Motivation t count is greater than t table (3.132 > 2.01290 ), from Job Satisfaction the calculated t is greater than the t table (2.463 > 2.01290) while the F test shows the calculated F value is 33.832 > F table 2.81 with a significance level of 0.000 < 0.05, so Ho is rejected and Ha is accepted. So it can be concluded that the variables of the Influence of the Work Environment, Work Motivation and Job Satisfaction on Employee Performance at the Riau Province Communication, Information and Statistics Service in 2023 have a positive and significant effect on Employee Performance both partially and simultaneously.